2021
DOI: 10.1021/acsagscitech.1c00118
|View full text |Cite
|
Sign up to set email alerts
|

Green Chemical Approach to Fabricate Hemp Fiber Composites for Making Sustainable Hydroponic Growth Media

Abstract: We report a water-based approach for making chemically reactive forms of hemp fibers and employing these materials to fabricate biocomposites for hydroponic applications. Our chemical strategy focused on coupling the lignin of hemp fibers and a bifunctional linker molecule (2-[(4-aminophenyl)­sulfonyl]­ethyl hydrogen sulfate) that contains an aromatic amine and a protected vinyl sulfone. The synthetic process started with converting the amine of this linker to an electrophilic diazonium ion, which then reacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…93 As well, in our previously reported study, we demonstrated the use of hemp fiber composite as plant growth media for hydroponics 94 (one type of soilless farming). 45 These aforementioned examples illustrate that hemp fiber composites have an exciting prospect due to their diverse and large arrays of practical applications. Hence, we expect that, due to its generalizability and applicability, this one-pot pectin-based fabrication methodology could serve as a benchmark for developing other technologies to accommodate a wide range of sustainable applications and provide eco-friendly alternatives to synthetic and nonbiodegradable petroleum-based products.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…93 As well, in our previously reported study, we demonstrated the use of hemp fiber composite as plant growth media for hydroponics 94 (one type of soilless farming). 45 These aforementioned examples illustrate that hemp fiber composites have an exciting prospect due to their diverse and large arrays of practical applications. Hence, we expect that, due to its generalizability and applicability, this one-pot pectin-based fabrication methodology could serve as a benchmark for developing other technologies to accommodate a wide range of sustainable applications and provide eco-friendly alternatives to synthetic and nonbiodegradable petroleum-based products.…”
Section: Discussionmentioning
confidence: 99%
“…70 Another successful strategy reported in several studies is the polymerization reaction involving lignin with bifunctional chemical linkers. 45 Research teams have also reported different types of lignin modifications using diazonium salts to obtain better adhesion to the polymer, which allow the creation of robust composites with better mechanical and thermal properties. [44][45][46] In addition, the phenolic hydroxyl groups of the lignin are good nucleophiles when compared to other possible hydroxyl groups available on the hemp fibers.…”
Section: Data Analysis Of Measured Physical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations